(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In this article you will get acquainted with preliminary scientific research conducted in the regions of Syrdarya and Jizzakh regions, as well as the results of various deflationary monitoring processes in the fight against wind erosion, reducing the impact of wind force on the soil, and irrigated lands in the region. The results of the experiment suggested planting protective crops to restore the fertility of deflated soils.